Parental adiposity differentially associates with newborn body composition. Issue 4 (19th December 2019) - Diaz, Eva C.; Cleves, Mario A.; DiCarlo, Marisha; Sobik, Sarah R.; Ruebel, Meghan L.; Thakali, Keshari M.; Sims, Clark R.; Dajani, Nafisa K.; Krukowski, Rebecca A.; Børsheim, Elisabet; Badger, Thomas M.; Shankar, Kartik; et al.
Summary: Background: Maternal obesity increases offspring's obesity risk. However, studies have not often considered maternal metabolic and exercise patterns as well as paternal adiposity as potential covariates. Objective: To assess the relationship between parental and newborn adiposity. Methods: Participants were mother‐child pairs (n = 209) and mother‐father‐offspring triads (n = 136). Parental (during gestation) and offspring (2 weeks old) percent fat mass (FM) were obtained using air displacement plethysmography. Maternal race, age, resting energy expenditure (indirect calorimetry), physical activity (accelerometry), gestational weight gain (GWG), gestational age (GA), delivery mode, infant's sex and infant feeding method were incorporated in multiple linear regression analyses. The association between parental FM and offspring insulin‐like growth factor 1 (IGF‐1) was assessed at age 2 years. Results: Maternal adiposity was positively‐associated with male (β = 0.11, P  = .015) and female (β = 0.13, P  = .008) infant FM, whereas paternal adiposity was negatively‐associated with male newborn adiposity (β = ‐0.09, P  = .014). Breastfeeding, female sex, GA and GWG positively associated with newborn adiposity. Vaginal and C‐section delivery methods associated with greater adiposity than vaginal induced delivery method. Plasma IGF‐1 of 2‐year‐old boys and girls positively associated with their respective fathers' and mothers' FM. Conclusions: Maternal and paternal adiposity differentially associate with newborn adiposity. The mechanisms of this finding remain to be determined.